FACTORS THAT AFFECT FINANCIAL DISTRESS IN INDONESIA - Susdaryo, Yoyo; Sofiati, Nunung Ayu; Kumaratih, Ita; Limakrisna, Nandan; Che Haat, Mohd Hassan; Muhammad, Zikri; Kusumawardani, Astrin; Saputra, Jumadil (International Journal of Research -GRANTHAALAYAH, 2021)
The results show that, it is proven that the variable liquidity and interest rates have a negative effect on financial distress. Meanwhile, the variables of Profitability, Leverage and Company Size have a positive effect on financial distress. While the Economic Stimulus variable is known to be the relationship between all variables of Liquidity, Profitability, Leverage, Company Size and Interest Rate on variables to Financial Distress. This means that company leaders must take into account liquidity, profitability, leverage, company size and interest rates to avoid financial distress.